HUBUNGAN JENIS KULIT DAN PENGGUNAAN KOSMETIK DENGAN TIPE MELASMA PADA WANITA USIA REPRODUKTIF DI WILAYAH KERJA UNIT PELAKSANA TEKNIS PUSKESMAS MEDAN DELI - JULIYANTI . (JURNAL ILMIAH MAKSITEK, 2023)
Melasma is defined as a chronic hyperpigmentation disorder that can be found in the dermis and epidermis. Melasma is commonly seen in women, especially of childbearing age, but can also affect adolescents, parents undergoing treatment, as well as idiopathic men. Morphologically, melasma appears symmetrical with uneven pigmentation, irregular margins in the center, cheeks and mandible. This study aims to determine the relationship between skin type and use of cosmetics with type of melasma in women of childbearing age. This type of research uses an analytic observational method with a cross sectional design. Frequency distribution of the most common type of melasma is found in the mixed type (42.3%), respondents with skin type IV (36.5%) , and respondents with a history of cosmetic use (63.5%). Spearman statistical test obtained p value < 0.05 for each variable. Based on the results of the statistical Spearman test that has been carried out, there is a significant relationship between skin type and use of cosmetics on the type of melasma with a p value obtained < 0.05, and the most dominant factors influencing the occurrence of melasma are hormonal and use of cosmetics.